Discrimination of enantiomers of amides with two stereogenic centers enabled by chiral bisthiourea derivatives using 1H NMR spectroscopy. Issue 30 (23rd July 2021) - Zhang, Hanchang; Zhao, Hongmei; Wen, Jie; Zhang, Zhanbin; Stavropoulos, Pericles; Li, Yanlin; Ai, Lin; Zhang, Jiaxin
Abstract : Enantiomers of amides with two stereogenic centers have been effectively discriminated in the presence of chiral bisthiourea derivatives as chiral solvating agents by 1 H NMR spectroscopy. Abstract : Enantiomers of a few new amides containing two stereogenic centers have been derived from d - and l -α-amino acids as guests for chiral recognition by 1 H NMR spectroscopy. A variety of chiral amides with two or more stereogenic centers often exist in the products of catalytic asymmetric synthesis, natural products or their total synthetic products, and chiral drugs. It would be a challenging and meaningful work to explore their chiral recognition. For this purpose, a class of novel chiral bisthiourea derivatives 1–9 has been synthesized from (1 S, 2 S )-(+)-1, 2-diaminocyclohexane, d -α-amino acids, and isothiocyanates as chiral solvating agents (CSAs). CSAs 1–9 proved to afford better chiral discriminating results towards most amides with two stereogenic centers, which have been rarely studied as chiral substrates by 1 H NMR spectroscopy. In particular, CSAs 7, 8 and 9, featuring 3, 5-bis(trifluoromethyl)benzene residues, exhibit outstanding chiral discriminating capabilities towards all amides, providing well-separated 1 H NMR signals and sufficiently large nonequivalent chemical shifts. To test their practical application in the determination of enantiomeric excess, 1 H NMR spectra of chiral amides (G16 ) with different optical purities were measured in the presence of CSAs 7 and 8, respectively. Their ee values (up to 90%) were accurately calculated by the integration of the NH proton of the CO NH Ph group of G16 . To better understand the chiral discriminating behavior, Job plots of (±)-G16 with CSA 7 and (±)-G17 with CSA 8 and the association constants ( K a ) of ( S, R )-G16 and ( R, S )-G16 with CSA 7 were evaluated, respectively. In order to further reveal any underlying intermolecular hydrogen bonding interactions, theoretical calculations of the enantiomers of ( S, R )-G16 and ( R, S )-G16 with CSA 7 were performed by means of the hybrid density functional theory (B3LYP) with the standard basis sets of 3-21G of the Gaussian 03 program, respectively.